A view on the long-run evolution of hours worked and labor productivity in Switzerland (1950 - 2010) - Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2012)
The discussion about the long-run evolution of labor productivity in Switzerland is flawed because the available data on the input of labor is incoherent and incomplete. It is the aim of this paper to establish a consistent aggregate series of total hours worked covering 1950-2010. The new data indicates that hours worked in Switzerland have been nearly stagnant between 1960 and 2005, implying that hours worked have grown considerably less than previously thought. As a direct consequence, Switzerland's performance in terms of labor productivity growth has been underestimated in previous work, particularly after the structural slowdown in labor productivity growth of 1973.
Keywords: J22; N34; O47; 330; Labor productivity; hours worked; working time; economic history of Switzerland; Arbeitsproduktivität; Arbeitszeit; Wirtschaftsgeschichte; Schweiz